LAND AS A “GOD”: THE GENDER DIMENSIONS OF ITS WEALTH CREATION AMONG THE DAGAABAS IN NORTHERN - WESTERN GHANA - Kpieta B. Alfred; Samuel Ziem Bonye (European Scientific Journal, ESJ, 2012)
The gender dimension of land as “god” and its wealth creation is what this study seeks to investigate. Among the peoples of Africa especially Ghana, there is a traditional concept of land worship which is linked up with land ownership. Significantly, the Ghanaian regards the earth as a “god” or “Mother Earth”, offering prayer in the form of libation pouring before cultivating the land and during harvest. Hence, data was collected through focus group discussions, key informant interviews, in-depth interviews and participant observation. The findings were that, in the Dagaaba people belief system, any person or group of persons that do not have the right to offer sacrifices to the earth „god‟ through the ancestors cannot own land. There are some calibers of persons especially women in the Dagaaba land that are said not to have an ancestor and therefore cannot sacrifice to the „land god‟ as a result of their spatial platform. Also, these classes of people cannot own some animals nor cultivate some crops that are classified as ritual animals and ritual crops. These belief systems are the basis of land tenure arrangements in the area and may have serious implication on wealth creation and ultimately affect development in the region.